2019
DOI: 10.1177/0093650219852857
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Socialization: An Actor-Partner Interdependence Model of Internet Self-Efficacy and digital Media Influence Between Parents and Children

Abstract: Media researchers have studied how parents and children influence and guide each other’s media use. Although parent and child socialization and influence are thought to be bidirectional, they are usually studied separately, with an emphasis on parental socialization, influence, and guidance of the child’s media use. In this article, we present results from a study that investigates perceived bidirectional digital media socialization between parents and children from the same household ( N = 204 parent-child dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 62 publications
0
6
0
3
Order By: Relevance
“…17 However, transactional theories of child development posit that there are bidirectional relationships between child characteristics and the caregiving environment (including household media use), which interact to shape child outcomes over time. 18 Although bidirectionality has been examined in the mediation literature, 19 only two studies have examined bidirectional relationships between media use and early childhood development and behavior. Cliff et al 20 found that more media exposure at 2 years was associated with weaker self-regulation at 4 years, whereas weaker selfregulation at 4 years was significantly associated with higher TV viewing, gaming, and media use at 6 years; however, effect sizes were small.…”
Section: Introductionmentioning
confidence: 99%
“…17 However, transactional theories of child development posit that there are bidirectional relationships between child characteristics and the caregiving environment (including household media use), which interact to shape child outcomes over time. 18 Although bidirectionality has been examined in the mediation literature, 19 only two studies have examined bidirectional relationships between media use and early childhood development and behavior. Cliff et al 20 found that more media exposure at 2 years was associated with weaker self-regulation at 4 years, whereas weaker selfregulation at 4 years was significantly associated with higher TV viewing, gaming, and media use at 6 years; however, effect sizes were small.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has examined bidirectional, integrated processes in parent-child relations with regard to technology and social media (Correa et al, 2013;Nelissen et al, 2019). Correa et al (2013) demonstrated that bottom-up socialization, or children socializing their parents, may be just as impactful on the family as a whole as top-down (parent-to-child) socialization.…”
Section: Bidirectional Relational Processes In Aosml Developmentmentioning
confidence: 99%
“…Correa et al (2013) demonstrated that bottom-up socialization, or children socializing their parents, may be just as impactful on the family as a whole as top-down (parent-to-child) socialization. Although parents may intend to employ certain digital media mediation strategies, those strategies may not be per-ceived by children the way they were intended, and children may use their own problem-solving skills to intentionally influence their own digital socialization (Nelissen et al, 2019). Updated understandings of parent mediation of media have incorporated bidirectional perspectives.…”
Section: Bidirectional Relational Processes In Aosml Developmentmentioning
confidence: 99%
“…Theoretical work has stated that instead of replacing one myopic view (parent-to-child) with another one (child-to-parent), it would be more fruitful to think of them together, in a continuous bidirectional framework. However, in media research, this has not really been explored explicitly apart from one study that found indications of bidirectional socialization between children and their parents in the context of digital media influence on each other (Nelissen, Kuczynski, Coenen, & Van den Bulck, 2019). This study used the actor-partner interdependence model to test parent and child effects simulations.…”
Section: Parent-child Bidirectionality In Interactions and Influence ...mentioning
confidence: 99%